(untitled) (Politeja, 2025)
The purpose of this article is to demonstrate the problems associated with Analytical Eclecticism, a method which was designed to be applicable in the field of international relations. As a philosophy of science, the method of Analytical Eclecticism created by Peter Katzenstein and Rudra Sil, which refers to pragmatism and the concept of Larry Laudan’s research programs, is a scientific stance according to which selected elements of different theories can be combined in order to acquire a deeper understanding of studied phenomena in international relations. The main premise of the article is that Analytical Eclecticism is a method that is rarely used, the reason for which is the insufficient attention its authors pay to its methodological aspects. The article also aims to introduce the methods used by pragmatists (including the principles of abductive inference), and by Laudan (the process of theoretical amalgamation), for a more thorough understanding which may make the AE method more accessible and perhaps more often used when conducting empirical research.